Neonatologists are using much less dexamethasone. Issue 5 (1st September 2003) - Shinwell, E S; Karplus, M; Bader, D; Dollberg, S; Gur, I; Weintraub, Z; Arnon, S; Gottfreid, E; Zaritsky, A; Makhoul, I R; Reich, D; Sirota, L; et al.
Abstract : Two historical cohorts (1993–1994 and 2001) of preterm infants ventilated for respiratory distress syndrome were compared. Dexamethasone administration fell from 22% to 6%. Chronic lung disease in survivors rose slightly from 13% to 17%, and mortality fell from 21% to 15% (other causes). The effect of restriction of dexamethasone use on chronic lung disease and mortality remains to be seen.